Colonial sovereignty and the intermittent order of silver things - Molina, J. Michelle (Religion, 2025)
This essay investigates the location of silver altarware around the church altar in colonial Mexico to tell a new materialist story about social ordering in this historical context. The article argues that in New Spain at the end of the eighteenth century, the body of Christ incarnate was a shape-shifting central force in this very hierarchical colonial society. The expectation that the mystical body of Christ was frequently (but not always) present in the Eucharist shaped the nature of contestation among the intermeshed yet competing colonial sovereignties of Church and State. Moreover, this spatio-material orientation to colonial power opened possibilities that those occupying a lower status might grab a piece of this sacramental power. This dynamic materialism followed a sacramental logics, a concept that names the way incarnational theology girds the scaffolding and propels the flow of power among competing colonial sovereignties.